A comparative in vitro study to evaluate the tensile strength of custom-milled fiber-reinforced resin posts and cores - بهرلي ناصر; محمود محمود (Latakia University Journal -Medical Sciences Series, 2023)
This study aims to evaluate the tensile strength of custom-milled fiber-reinforced resin posts and cores fabricated by CAD/CAM technology, compared to prefabricated fiber reinforced resin posts and cores). MATERIALS AND METHODS: 20 mandibular premolars were collected, and the coronal part was cut 2 mm above the cemento-enamel junction. Endodontic treatment was performed. Then the samples were placed within acrylic bases. After that the root canals were prepared to receive the posts. the samples were randomly distributed into two groups: group 1: restored with custom milled resin fiber-reinforced posts and cores group 2: restored with prefabricated fiber-reinforced resin posts and composite cores buildups The samples were subjected to pull out forces using the general mechanical testing machine, as a pulling force was applied parallel to the longitudinal axis of the tooth at a speed of 1 mm/min until failure occurred. Statistical tests were carried out using the SPSS (20). Results: The T student’s test showed that there were statistically significant differences between the mean tensile strengths between the two groups (P = 0.039 > 0.05). Conclusion: Within the limits of this study, the custom milled resin fiber-reinforced posts and cores fabricated by CAD/CAM technology showed greater retention than the prefabricated resin posts.